A contribuição do Sci-Hub no acesso à literatura científica e na disseminação do conhecimento acadêmico - Klein, Luiza (Universidade Federal de São Carlos, 2025)
Scientific knowledge is essential to science and society’s progress, and its access, public and free, makes it possible to evaluate and contest scientific discovery. Facing the emergence of paywalls, the movement of Open Science surges focusing on the promotion of free-barrier knowledge. Based on this context, this project raises the following question: What is Sci-Hub’s contribution to the access of scientific literature and the dissemination of academic knowledge? The general objective is to discuss Sci-Hub's contribution to democratizing access to scientific communication for the development of science, in order to delve into the contribution of Open Science and open access, the analysis of copyright and property rights in open access and to present Sci-Hub as an alternative means of retrieving articles. The research has an applied nature, a qualitative approach and exploratory objectives, also using bibliographic and documentary research to carry out a case study, to obtain results with a categorical content analysis. Twelve papers were analyzed, 6 dissertations and 6 theses from the Special Education postgraduate program at the Federal University of São Carlos (UFSCar). Of the 457 journal articles evaluated, 260 were categorized as closed or hybrid access and, of these, 169 articles from closed access journals were not found on Sci-Hub. It was concluded that Sci-Hub's contribution to the access of scientific literature and the dissemination of academic knowledge in the area studied is less than expected, since the use of federal services, such as the Federated Academic Community Network (CAFe), facilitates access through official channels, in which the alternative means are not needed in every case.
Sci-Hub's contribution to accessing scientific literature and disseminating academic knowledge
Keywords: Sci-Hub; Acesso aberto; Ciência aberta; Direito autoral; Direito patrimonial; Open access; Open science; Copyright; Patrimonial rights; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA